1994
DOI: 10.1139/e94-117
|View full text |Cite
|
Sign up to set email alerts
|

Effet de la vitesse de refroidissement sur l'intensité de l'aimantation thermorémanente: étude expérimentale, conséquences théoriques

Abstract: The experiments reported here compare intensity and thermal resistance of two thermal remanent magnetizations (TRM), successively acquired by the same sample under a magnetic field, but at two different cooling speeds. The samples (one with a base of CrO2 powder, and the others derived from oceanic basalts) were representative of the different types of structure domains characteristic of magnetic grains. The experimental procedure established aimed at limiting the various factors of uncertainty: mineralogical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
2
11
1
Order By: Relevance
“…This prediction has been experimentally confirmed by studies on archeological baked clay [Fox and Aitken, 1980] and on SD hematite [Papusoi, 1972a]. The same trend was confirmed for PSD size grains in baked clays, potsherds, and volcanic rocks [Yang et al, 1993;Biquand, 1994;Chauvin et al, 2000]. However, exactly the opposite trend was observed for MD magnetite [Papusoi, 1972b] (see also McClelland-Brown [1984]; Perrin [1998]) and remains unexplained.…”
Section: Af Demagnetization Of Arms With Different Acquisition Decay mentioning
confidence: 60%
“…This prediction has been experimentally confirmed by studies on archeological baked clay [Fox and Aitken, 1980] and on SD hematite [Papusoi, 1972a]. The same trend was confirmed for PSD size grains in baked clays, potsherds, and volcanic rocks [Yang et al, 1993;Biquand, 1994;Chauvin et al, 2000]. However, exactly the opposite trend was observed for MD magnetite [Papusoi, 1972b] (see also McClelland-Brown [1984]; Perrin [1998]) and remains unexplained.…”
Section: Af Demagnetization Of Arms With Different Acquisition Decay mentioning
confidence: 60%
“…In particular, both Papusoi [1972a] and Fox and Aitken [1980] found that the slowly cooled (∼10 −3 K/s) magnetization was 5%-14% larger than the rapidly cooled (∼1 K/s) magnetization. Nearly the same outcome was confirmed for pseudo-single-domain-(PSD-) sized grains in baked clays or potsherds and glasses in volcanic rocks [e.g., Yang et al, 1993;Biquand, 1994;Genevey and Gallet, 2002;Genevey et al, 2003;Morales et al, 2006aMorales et al, , 2006bFerk et al, 2010]. However, exactly the opposite trend of lower magnetization for slower cooling was observed for multidomain (MD) magnetite [Papusoi, 1972b;Brown, 1984;Perrin, 1998] and remains poorly understood.…”
Section: Thellier Modelingmentioning
confidence: 77%
“…This effect is predicted by Néel's theory [ Néel , 1955; see also Dodson and McClelland‐Brown , 1980; Halgedahl et al , 1980] for single domain grain assemblages. It was further studied for different types of domain grains and experimentally observed for both volcanic products and archeological artifacts [e.g., Fox and Aitken , 1980; Biquand , 1994; Chauvin et al , 2000; Leonhardt et al , 2006]. This cooling rate effect is due to the fact that the cooling of the samples in the laboratory is typically faster than the original cooling.…”
Section: Diversity Of the Experimental Methodsmentioning
confidence: 99%